Effect of venous foot pump intervention on prevention of venous thromboembolism in patients with major orthopedic surgery: a systematic review and meta-analysis - Tong, Yahui; Ying, Rulan; Niu, Meier; Xu, Lan (Frontiers in Cardiovascular Medicine, 2024)
Background: Venous thromboembolism (VTE) is a common complication after major orthopedic surgery. The venous foot pump (VFP) is an effective mechanical preventive measure against VTE in patients. However, the differences in effectiveness based on varying usage times of VFP remain unclear.Objective: To explore the effectiveness of VFP with different usage times in preventing VTE in patients undergoing major orthopedic surgery.Methods: Nine databases (PubMed, Web of Science, CINAHL, Embase, Cochrane Library, CBM, VIP, CNKI, and Wanfang) were searched to identify randomized controlled trials (RCTs) evaluating VFP interventions for VTE prevention in major orthopedic surgery patients. The risk of bias in each study was assessed using the Cochrane Collaboration tool. Meta-analysis was conducted using RevMan 5.3.Results: A total of 36 RCTs involving 3,791 patients undergoing major orthopedic surgery were included. Meta-analysis revealed significant differences in VTE incidence between the VFP and blank control groups (RR = 0.27, 95% confidence interval CI: 0.19-0.38, P < 0.001) and between the VFP plus chemoprophylaxis and chemoprophylaxis alone groups (RR 0.39, 95% CI: 0.29-0.53, P < 0.001).However, no statistically significant difference was observed between the VFP and the LMWH groups (RR= 0.93, 95% CI: 0.54-1.61, P = 0.8). Subgroup analysis showed no significant difference in effectiveness based on different VFP usage durations (VFP versus Blank: Chi-square = 0.54, P = 0.46, I 2 = 0%; VFP Plus chemoprophylaxis versus chemoprophylaxis alone: Chi-square = 1.93, P = 0.86, I 2 = 2 / 15 0%).The current evidence indicates that VFP significantly reduces the incidence of postoperative VTE in patients undergoing major orthopedic surgery. VFP can be considered an add-on strategy to LMWH for patients at low risk of bleeding and an alternative strategy to LMWH in patients at high risk of bleeding. This study found no significant difference in effectiveness between various VFP usage interventions. Future research should focus on economic cost-effectiveness and patient acceptance to help policymakers determine the most efficient usage duration, providing practical guidance for thromboprophylaxis.